Women in science's family and career expectations, intentions and decisions: how do they evolve over the graduate and early career years? - Stevens, Sarah, author; Canetto, Silvia Sara, advisor; Gibbons, Alyssa, committee member; Kees, Nathalie, committee member (Colorado State University. Libraries, 2014)
A wide body of research has documented that women drop out of science at each successive stage of education and career, a phenomenon known as the leaky pipeline (Goulden, Frasch & Mason, 2009). This phenomenon is especially evident in Atmospheric Science (ATS), a group that loses women at a higher rate than other geoscience fields (NSF, 2013). One reason for this loss is the stress of education and career on family planning and vice versa (Thiry, 2011). This conflict is particularly intense for women in dual-career relationships, perhaps related to a socialized pressure to prioritize their relationships over their careers (Canetto, Trott, Thomas, & Wynstra, 2012; Larocque, 1995). One limitation of prior studies is that they are cross-sectional. No previous research has longitudinally examined the work and family choices and experiences of female ATS graduate students. This study will do so by investigating how female graduate students in ATS think about commitment to one's partner and make decisions about job location.